Effects of Ultrasonic Vibration on the Transport Coefficients in Plasma Arc Welding - Yongfeng Li (Metals, 2020)
In ultrasound assisted plasma arc welding (U-PAW), the exerted ultrasonic vibration on the tungsten electrode interacts with the plasma arc and changes its heat-pressure characteristics. It is of great significance to investigate the underlying interaction mechanism. In this study, the calculation method of transport coefficients in U-PAW is developed. Translational thermal conductivity (including electrons thermal conductivity and the thermal conductivity of heavy particles) and electrical conductivity are calculated by considering the second-order approximation of Maxwell velocity distribution function, while the method of Butler et al. is adopted to calculate the reaction thermal conductivity in U-PAW. The effective value of the ultrasound velocity gradient tensor is employed to describe the effects of ultrasonic vibration on transport coefficients in ultrasound assisted plasma arc. The calculation results show that when the ultrasound is applied, the thermal conductivity of heavy particles in the plasma increases significantly and the electron thermal conductivity increases within some extent. The thermal conductivity of the reaction also increased to a great extent, and the electrical conductivity decreases a little bit. Although the thermal diffusion coefficient also has some increase, but the ordinary diffusion coefficient is obviously reduced due to the application of the ultrasound. With the updated transport coefficients, the plasma arc pressure on the anode surface is numerically computed, and the predicted pressures of PAW and U-PAW can be consistent with the measured ones.